DESIGN PROTOTYPE OF SMART DETECTOR ENVIRONMENT SYSTEM ON SEMICONDUCTOR DETECTOR STORAGE (HPGE) - Rindi Wulandari (Journal of Green Science and Technology, 2022)
The HPGe detector is a device that should be cooled when used and can be operated at room temperature. For this reason, it is necessary to monitor the temperature and humidity in the HPGe detector storage area to produce optimal performance. This research was focused on designing a Smart Detector Environment System as a means of monitoring and automatic control of temperature and humidity in the HPGe detector storage. Temperature and humidity detection in the system was carried out by the DHT22 sensor connected to Arduino Uno and the motor driver module. Arduino uno gave the command "00000011" to detect the temperature in the chamber, and "00000101" to start the detection of humidity in the chamber, then the data generated by the DHT22 sensor would be displayed and processed by LabVIEW, which was used to move the fan to regulate the temperature and humidity in the system with the condition that the lamp on the chamber was left on (manual).Â  The results obtained were in the form of a design and automatic control of temperature and humidity monitoring and control in the HPGe detector storage whose temperature could be adjusted automatically according to the needs of the HPGe detector.